Aspects of the formation of tin oxide under annealing of nanopowders obtained by pulsed laser ablation of metallic tin in aqueous media - Fakhrutdinova, Elena D. (Russian physics journal)
Nanocolloids, obtained by pulsed laser ablation (Nd:YAG laser, 1064 nm, 7 ns, 150 mJ) of metallic Sn in distilled water and also in solutions of hydrogen peroxide and nitric acid, were dried and subjected to heat treatment at different temperatures up to 800°С. It has been shown that addition of H2O2 or HNO3 has an effect not only on the size characteristics and structure of the initial nanoparticles, but also on the process of formation and the final characteristics of SnO2 under annealing. By the method of powder x-ray diffraction it was established that in the case of pulsed laser ablation in water and in a solution of nitric acid, the initial particles contain the phase SnO, but for annealed sample obtained by ablation in HNO3, an intermediate orthorhombic phase of SnO2 is formed. Additional studies using Raman spectroscopy and thermal analysis made it possible to determine the presence of tin hydroxide in the initial samples and formation of intermediate forms of its oxides, SnOx, upon annealing. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.